2015
DOI: 10.1016/j.ijheh.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of cord to maternal serum PCB concentrations in relation to their congener-specific physicochemical properties

Abstract: The aim was to characterize placental transfer of some congeners of polychlorinated biphenyls (PCBs) and to relate human in utero exposure to these pollutants to their physicochemical properties. We included into the study 1134 births during the period 2002–2003 from two highly PCB contaminated districts in eastern Slovakia. Concentrations of 15 PCB congeners (IUPAC No. 28, 52, 101, 123+149, 118, 114, 153, 105, 138+163, 167, 156+171, 157, 180, 170, and 189) in umbilical cord (C) and maternal serum (M) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 98 publications
2
35
0
Order By: Relevance
“…In secondary analyses using this value, we derived a ratio of 1.94, which was not meaningfully different from our ratio of 2.18 (data not shown). Here and in our study (Lancz et al, 2015), the lipid level might have been influenced by labor. Furthermore, in some of the reviewed papers the authors reported that blood and milk samples from the same individual were not collected at the same time.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…In secondary analyses using this value, we derived a ratio of 1.94, which was not meaningfully different from our ratio of 2.18 (data not shown). Here and in our study (Lancz et al, 2015), the lipid level might have been influenced by labor. Furthermore, in some of the reviewed papers the authors reported that blood and milk samples from the same individual were not collected at the same time.…”
Section: Discussionsupporting
confidence: 41%
“…With HCB serum concentration expressed as wet weight, we calculated the concentration of total lipids in serum as 10 mg lipids/ml serum. We observed this value in 1065 subjects (Lancz et al, 2015) (Table 2). The descriptive statistical data on total lipid concentration in mother and cord serum samples are shown in Table 2 (Lancz et al, 2015).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Nearly all PCBs are found in higher levels in maternal than cord serum (90), with the exception of only a few congeners (91). One recent study suggested that lower chlorinated PCB congeners have a higher maternal-fetal transfer rate compared to higher chlorinated congeners (92) but this pattern is not supported by a systematic review and other studies (90,93,94). As PCB congener molecular weight (92,94) or lipophilicity (94) increase, placental transfer decreases.…”
Section: Placental Transfer and Fetal Burdenmentioning
confidence: 91%